Efficient contracting and fair play in a simple principal-agent experiment - Vital Anderhub; Simon Gächter; Manfred Königstein (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
Modern 'principal-agent theory' has made a lot of progress in proposing theoretical Solutions to agency problems. This paper contributes to a better understanding of behavior in agency situations. In particular, we provide experimental evidence on offered contracts and effort choices in a simple agency game. In line with principal-agent theory we find that in our experiments many contracts proposed by principals are 'incentive compatible' and most agents behave optimally given the terms of the contract. However, in contrast with economic predictions, we find that agents (i) reject 'unfair contracts' and that (ii) given acceptance, their effort choices are to some extent driven by reciprocity. It seems that contract design has to regard an equity constraint that has so far been neglected by contract theory. In fact, most contract offers observed in the experiment aim at fair surplus sharing.
urn:nbn:de:kobv:11-10046691
Keywords: J33; J41; L14; C91; 330; principal-agent theory; contract theory; fair sharing; incentive contracts; reciprocity; experiments